2006
DOI: 10.1016/j.peptides.2006.01.018
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of the viral peptide linked to the genome (VPg) of poliovirus

Abstract: VPgs are essential for replication of picornaviruses, which cause diseases such as poliomyelitis, foot and mouth disease, and the common cold. VPg in infected cells is covalently linked to the 5' end of the viral RNA, or, in a uridylylated form, free in the cytoplasm. We show here the first solution structure for a picornaviral VPg, that of the 22-residue peptide from poliovirus serotype 1. VPg in buffer is inherently flexible, but a single conformer was obtained by adding trimethylamine N-oxide (TMAO). TMAO h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 59 publications
0
36
0
1
Order By: Relevance
“…These structures are surprising in several ways. We find that the VPg proteins of FCV and MNV contain ␣-helical cores flanked by long unstructured termini, in contrast to the intrinsically disordered nature of smaller picornavirus VPg (49) and the larger VPg proteins from RNA viruses of plants, such as potyvirus (52,54). Although there is some evidence (from circular dichroism measurements, protease sensitivity assays, and NMR analyses) for the presence of a compact domain within potyvirus VPg, a defined tertiary structure has not been detected; rather, the core within this protein appears to have the properties of a dynamic molten globule (54).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These structures are surprising in several ways. We find that the VPg proteins of FCV and MNV contain ␣-helical cores flanked by long unstructured termini, in contrast to the intrinsically disordered nature of smaller picornavirus VPg (49) and the larger VPg proteins from RNA viruses of plants, such as potyvirus (52,54). Although there is some evidence (from circular dichroism measurements, protease sensitivity assays, and NMR analyses) for the presence of a compact domain within potyvirus VPg, a defined tertiary structure has not been detected; rather, the core within this protein appears to have the properties of a dynamic molten globule (54).…”
Section: Discussionmentioning
confidence: 74%
“…The solution structures of the 22-amino-acid VPg from poliovirus, a picornavirus, have been determined using nuclear magnetic resonance (NMR) spectroscopy for both the native peptide and VPg that has been nucleotidylated on its acceptor Tyr 3 residue (48,49). In its native form, poliovirus VPg appears to be highly flexible; a defined conformation was observed only in the presence of high concentrations (1 M) of the organic solvent trimethylamine N-oxide (TMAO).…”
mentioning
confidence: 99%
“…Two of the models, based on mutation and computation studies, assume that VPg and the VPg precursor 3AB bind to the same surface on 3D pol and conclude that VPg enters the polymerase active site from the back of the polymerase molecule (45,46). In contrast, structural evidence from the FMDV 3D pol -VPg complex suggests an alternative arrangement, since the last ordered residues at the carboxyl end of VPg are seen to bind to the front face of 3D pol .…”
Section: Vol 81 2007 Crystal Structure Of Poliovirus 3cd Protein 3591mentioning
confidence: 99%
“…The nuclear magnetic resonance structure of PV VPg in solution has shown that it is intrinsically flexible in low-salt buffer (58). A major conformational change was observed in a stabilizing solution, perhaps mimicking induced folding upon binding to 3D pol (58). Concerning the VPg-binding site on 3D pol , two different sites seem to coexist.…”
mentioning
confidence: 99%